The effect of physiotherapy on body balance and pain intensity of elite female handball player after anterior cruciate ligament reconstruction and medial meniscus fixation: A case study - Ramanauskas, M.; Bikuliciene, R.; Jotkeviciute, E. (2021 International Conference BIOMDLORE, 2021)
Knee injuries are relatively common in court- and field-based sports. Anterior cruciate ligament (ACL) and meniscus injuries often require surgical treatment to return to high-level sports. ACL tears after reconstruction surgery carry a high recurrence rate. Balance training plays an important role in injury prevention programmes and is important to improve lower extremity function and decrease the risk of recurring knee injury. The research aim is to evaluate the effect of physiotherapy for an elite female handball player`s body balance and pain intensity after anterior cruciate ligament reconstruction and medial meniscus fixation. Body balance was evaluated with the Posturomed platform with two-dimensional measurement by MicroSwing software. Pain intensity was measured using the Visual Analogue Scale (VAS). A physiotherapy programme with an unstable oscillatory platform was developed and used to train the athlete`s body balance. Posturomed platform oscillations decreased from 34.1 cm to 16 cm in the frontal plane on the left leg and from 46 cm to 24.4 cm on the right leg; in the sagittal plane the platform distance changed from 273 cm to 256 cm on the left leg and 207 cm to 211 cm on the right leg. The average platform disturbance in the frontal plane was 22.73 ± 6.75 cm on the left leg and 31.21 ± 9.37 cm on the right; the average disturbance path in the sagittal plane was 254.5 ± 61.48 cm on the left leg and 223 ± 37.56 cm on the right leg. Balance stability increased from 55% (right leg) and 65% (left leg) to 89% (right leg) and 88% (left leg). During 6 weeks of intervention the pain intensity score changed from 7 to 3 (VAS). The six-week physiotherapy programme with an unstable oscillatory platform (Posturomed) improved body balance and decreased the pain intensity.